In memoriam: Fedir Vlasovych Dakhno (June 19, 1939 – May 4, 2019) - Editorial Board Problems of Cryobiology; Cryomedicine, Editorial Board Problems of Cryobiology (Problems of Cryobiology and Cryomedicine, 2019)
-